THE MODERATING ROLE OF ORGANIZATIONAL SUPPORT ON THE RELATIONSHIP OF PROBLEM SOLVING AND TASK COMPLEXITY TO WORK ENGAGEMENT - Gabriel Angela Purba; Anwar Mansyur (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study explores the moderating role of organizational support in the relationship between problem-solving ability, task complexity, and employee work engagement. The dynamics of the contemporary work environment demand an in-depth understanding of the factors that influence work engagement as a central construct in human resource management. Using a quantitative approach with a cross-sectional survey design, this study analyzed data through variance-based structural equation modeling to test the formulated moderation hypotheses. The findings show that problem-solving ability and task complexity positively influence work engagement. Organizational support was shown to moderate the relationship significantly between problem-solving ability and work engagement, but the moderating effect on task complexity was not significant. The theoretical contribution of the study lies in validating the moderating mechanism of organizational support in optimizing individual competencies to increase work engagement. Practical implications indicate the importance of developing an integrated organizational support system that includes instrumental and emotional dimensions to facilitate the transformation of employees' analytical abilities into active engagement in an increasingly complex work environment. Keywords: Work Engagement; Organizational Support; Problem Solving Ability